2014
DOI: 10.1175/jcli-d-12-00139.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Impact of Wind Intensification on Antarctic Sea Ice Volume

Abstract: A global sea ice-ocean model is used to examine the impact of wind intensification on Antarctic sea ice volume. Based on the NCEP-NCAR reanalysis data, there are increases in surface wind speed (0.13% yr 21 ) and convergence (0.66% yr 21 ) over the ice-covered areas of the Southern Ocean during the period 1979-2010.Driven by the intensifying winds, the model simulates an increase in sea ice speed, convergence, and shear deformation rate, which produces an increase in ridge ice production in the Southern Ocean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…This behaviour is consistent with winds being the main driver of Antarctic sea-ice increases 17 . The WALL simulation is also more consistent with the observed increase in Antarctic sea-ice area between 1979 and 2007 than the CORE2 ARTICLE simulation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This behaviour is consistent with winds being the main driver of Antarctic sea-ice increases 17 . The WALL simulation is also more consistent with the observed increase in Antarctic sea-ice area between 1979 and 2007 than the CORE2 ARTICLE simulation.…”
Section: Resultssupporting
confidence: 88%
“…Recently, observations and modelling have highlighted the importance of wind variability in accounting for the behaviour of Southern Hemisphere sea-ice 10,[15][16][17][18][19] . Originally, it was argued that trends in dynamics and thermodynamics linked to local winds were responsible for producing the regional sea-ice trends in most sectors of the Southern Ocean 16 .…”
mentioning
confidence: 99%
“…A modelling study [50] has suggested that the recent increase of wind speed and convergence in the sea ice zone may have increased ridging production, leading to an increase in volume of thick ice, although it is not possibly to verify this at present. Hopefully, future developments will allow sea ice thickness to be routinely monitored allowing the investigation of changes in ice volume.…”
Section: Conclusion and Future Work Requiredmentioning
confidence: 99%
“…Atmospheric reanalysis daily data were taken from the European Centre for Medium-Range Weather Forecasts (ECMWF) Interim gridded data product over 1995-2014(Dee and others, 2011. We used mean sea-level pressure (MSLP), geopotential height (1000,975,950,925,900,850,800,750,700,650,600,550, 500 hPa), 2 m temperature (T2m), and meridional component of 10 m wind (V10m) at 2°× 2°latitude/longitude resolution, for ease of computation and acknowledging that features of interest are of large spatial scale, from meso-α to synoptic scale.…”
Section: Atmospheric Datamentioning
confidence: 99%
“…Indices were averaged for the 3 months of July, August and September, with the threshold ±0.5°C (ENSO)/standard deviations (SAM) take as the cutoff for positive and negative 'events' according to NOAA/NWSCPC (Table 1). Based on the above index values, four El Niño years (1997,2002,2004, 2009), seven La Niña years (1995( , 1998( , 1999( , 2000( , 2007( , 2010( ), nine ENSO-neutral years (1996( , 2003( , 2005( , 2006( , 2012( , 2013( , 2014, six SAM positive years (1997,1998,2004,2008,2010,2012), eight SAM negative years (1995,1996,2000,2002,2007,2009,2011,2013) and six SAM-neutral years (1999,2001,2003,2005,2006,2104) were selected for analyses in this study.…”
Section: Enso and Sam Index Datamentioning
confidence: 99%